Interpellation Mechanism In Jian Rong’s Wolf Totem - Yudhanita Pertiwi; Sri Saraswati; Yanuaresti Kusuma Wardhani (Journal of Innovative and Creativity, 2025)
This paper explores the concept of ideology through the lens of Louis Althusser's theories, particularly interpellation, experienced by Chen Zen in Jiang Rong’s Wolf Totem. The purpose of this research is to go beyond oversimplified ideas of false consciousness and investigate how ideology essentially influences people's worldviews, directs group behaviour, and pervades every facet of human existence, from government system to personal identities. The research was carried out using descriptive qualitative method. It meticulously analyzes the novel Wolf Totem by Jiang Rong to demonstrate Althusser's concepts in practice. The results and discussion focus on how the protagonist, Chen Zhen, a Han Chinese student in Inner Mongolia, experiences a profound ideological shifting. Through his engagement in Mongolian culture and his observations of wolves, Chen's previous "tired and weary" identity is gradually replaced by a new perspective, symbolizing the "wolf's blood" flowing in his blood. This shift is an example of the unconscious process of interpellation, in which people are "hailed" into particular subject positions, which eventually serves to either support or undermine pre-existing social structures. In conclusion, the paper demonstrates how Wolf Totem vividly illustrates the dynamic interaction between state-imposed ideology and alternative cultural ideologies, revealing how they shape identities, worldviews, and social relations. This analysis ultimately advances our knowledge of conflict and collaboration in a complex world